Incidence of cancer among vinyl chloride and polyvinyl chloride workers. Issue 1 (February 1984) - Heldaas, S S; Langård, S L; Andersen, A
Abstract : The results of a follow up study of the incidence of cancer and the mortality in a cohort of 454 male workers producing vinyl chloride and polyvinyl chloride are presented. The study population was restricted to employees with more than one year's work experience in the study plant between 1950 and 1969 and the cohort was followed up from 1953 to the end of 1979. Twenty three new cases of cancer were observed compared with 20.2 expected; one case of liver angiosarcoma was found. Five cases of lung cancer were found (2.8 expected) and four cases of malignant melanoma of the skin were observed (0.8 expected). The possibility of a causal relationship between exposure to vinyl chloride and the development of malignant melanomas is discussed.